Pengaruh Kompetensi Sumber Daya Manusia Dan Pemanfaatan Teknologi Informasi Terhadap Kualitas Laporan Pertanggungjawaban Bantuan Operasional Penyelenggaraan (BOP) Pada Taman Kanak-Kanak Di Kecamatan Masbagik - Tiara Apriliani; Animah Animah; Rini Ridhawati (Jurnal Riset Mahasiswa Akuntansi, 2026)
This study aims to analyze the influence of human resource competency and information technology utilization on the quality of accountability reports for operational assistance in kindergartens in Masbagik District. The variables used in this study are human resource competency, information technology utilization, and the quality of accountability reports for operational assistance in kindergartens in Masbagik District. This study uses primary data obtained through distributing questionnaires to respondents. The population in this study were school principals, school treasurers, and school operators in kindergartens in Masbagik District. The sampling technique used was purposive sampling with a sampling result of 128 respondents. The data analysis tool used was Statistical Program for Social Science (SPSS) version 25. The data analysis technique used descriptive statistical testing, data validity and reliability testing, classical assumption tests (normality, multicollinearity, heteroscedasticity tests), and multiple linear hypothesis testing. The results of this study indicate that human resource competency and information technology utilization significantly influence the quality of operational assistance accountability reports, partially, while simultaneously, human resource competency and information technology utilization significantly influence the quality of operational assistance accountability reports. The implications of this study can be used as a knowledge contribution for educators in Masbagik District regarding the quality of operational assistance accountability reports. By considering both human resource competency and information technology utilization, the quality of operational assistance accountability reports in kindergartens can be improved.